2016
DOI: 10.1016/j.rehab.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel activity monitor in impaired, slow-walking, crutch-supported patients

Abstract: This is the first validation study to assess physical activity with an AM in impaired, slow-walking, crutch-supported patients. The AM was a valid tool for measuring physical activity in these patients. The tool may help in evaluating and optimizing rehabilitation programs for patients after TJA, those recovering from stroke or chronic impaired patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…The position of the sensor was at the mid-thigh between the trochanter and lateral condyle, with the y-axis of the sensor along the axis of the femur (van Laarhoven et al. 2016). The sensor was worn during waking hours for a minimum of 8 hours per day.…”
Section: Methodsmentioning
confidence: 99%
“…The position of the sensor was at the mid-thigh between the trochanter and lateral condyle, with the y-axis of the sensor along the axis of the femur (van Laarhoven et al. 2016). The sensor was worn during waking hours for a minimum of 8 hours per day.…”
Section: Methodsmentioning
confidence: 99%
“…Outcome consisted of quantitative parameters (time spent walking and cycling in seconds, the number of steps and sit-stand transfers) and qualitative parameters (cadence in steps per minute and high-intensity peak counts in numbers). This technique was clinically validated by Lipperts et al 35 and van Laarhoven et al 36 in healthy subjects and subjects who had undergone unilateral total joint arthroplasty, using video observation as the gold standard. The studies showed an excellent accuracy (>97%) in determining activity levels with this technique in a semi-free setting.…”
Section: Methodsmentioning
confidence: 99%
“…For this study intensity peak counts were accounted for events <2, ≥2, ≥3, and ≥8 g. This classification was chosen as events more than equal to 2 g do not usually appear during normal activities like walking but are common with impacts from, for example, sports or stumbles. The AM method used was found to work reliably in identifying activities in a semi‐free setting compared to human observers, with a classification accuracy of more than 97% 21,22 . In addition, activity monitoring following this or similar protocols has shown its value for research and outcome assessment in current literature 23,24 …”
Section: Methodsmentioning
confidence: 96%